The System of Product Marketing Base on Mobile in Micro Small and Medium Enterprises of Dekranasda Tanggamus Regency - Yuntriani Yuntriani; Adinca Rahma Dewi (Institut Bakti Nusantara, 2020)
Tanggamus Regency is one of the in Lampung Province, the most of income of them is trade, so that it product a various, such as a good product and service. Dekranasda of Tanggamus have a product by handcrafts which the marketing of process is of Dekranasda still manual, so it’s known by the public, there for they must have a good strategy to increase competitiveness with information utilizing with e-commerce application system by mobile based. So that this system can develop product marketing, product transaction as well as information about micro small and medium enterprises, Dekranasda of Tanggamus Regency, so that able to access by public in indoesian or foreign countries. The Development this e-commerce system using waterfall model with trough steps such as analysis, desain, coding, implementation, and system maintenance. So, with the formation of e-commerce dekranasda of tanggmus can be a fool for buying and selling transactions for costumer and ca be used as a promotional media od Dekranasda Tanggamus Regency.